Roothairless5, which functions in maize (Zea mays L.) root hair initiation and elongation encodes a monocot-specific NADPH oxidase - Nestler, Josefine; Liu, Sanzhen; Wen, Tsui-Jung; Paschold, Anja; Marcon, Caroline; Tang, Ho Man; Li, Delin; Li, Li; Meeley, Robert B.; Sakai, Hajime; Bruce, Wesley; Schnable, Patrick S.; et al. (My University, 2014)
Root hairs are instrumental for nutrient uptake in monocot cereals. The maize (Zea mays L.) roothairless5 (rth5) mutant displays defects in root hair initiation and elongation manifested by a reduced density and length of root hairs. Map-based cloning revealed that the rth5 gene encodes a monocot-specific NADPH oxidase. RNA-Seq, in situ hybridization and qRT-PCR experiments demonstrated that the rth5 gene displays preferential expression in root hairs but also accumulates to low levels in other tissues. Immunolocalization detected RTH5 proteins in the epidermis of the elongation and differentiation zone of primary roots. Because superoxide and hydrogen peroxide levels are reduced in the tips of growing rth5 mutant root hairs as compared to wild-type, and ROS is known to be involved in tip growth, we hypothesize that the RTH5 protein is responsible for establishing the high levels of ROS in the tips of growing root hairs required for elongation. Consistent with this hypothesis, a comparative RNA-Seq analysis of 6-day-old rth5 versus wild-type primary roots, revealed significant over-representation of only two gene ontology (GO) classes related to the biological functions (i.e., oxidation/reduction and carbohydrate metabolism) among 893 differentially expressed genes (FDR <5%). Within these two classes the subgroups “response to oxidative stress” and “cellulose biosynthesis” were most prominently represented.
Citation: Nestler, J., Liu, S., Wen, T. -., Paschold, A., Marcon, C., Tang, H. M., et al. (2014). Roothairless5, which functions in maize (zea mays L.) root hair initiation and elongation encodes a monocot-specific NADPH oxidase. Retrieved from krex.k-state.edu.
Keywords: Maize; Root hairs; rth5; NADPH oxidase; RNA-Seq